The perceived impact of entrepreneurial coaching in the decision making of entrepreneurs within South African SMMEs - Bloem, Sebastian (My University, 2022)
This research study was undertaken to investigate the effectiveness and perceived impact of entrepreneurial coaching on the decision-making of entrepreneurs in the small, medium, and micro enterprise sector in South Africa. A sequential mixed method study was undertaken. The starting point was the distribution of self-administered quantitative survey questionnaires to 148 participants selected according to probability sampling first, and then purposive sampling in the qualitative section. The data collected was analysed using Correlational Analysis, Regression Analysis and Exploratory Factor Analysis. The second and qualitative phase of the study consisted of two parts: The first, was an action research intervention. It took the form of coaching sessions that were conducted with seven participants from the first larger study. Thereafter, interviews were conducted with coaching participants. The findings of the quantitative phase showed that decision-making positively impacts business growth. In the second phase of the study, the qualitative phase, it was evident that an entrepreneurial coaching intervention enhanced the decision-making of entrepreneurs. The recommendation to those who support SMMEs is to increase the utilisation of entrepreneurial coaching to aid in the arrest of the failure rate of SMMEs; and for the entrepreneur entrepreneurial coaching can deliver numerous benefits, like improved self-efficacy and improved decision-making, which leads to business growth and sustainability.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Business and Executive Coaching to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2022
Keywords: Entrepreneurial coaching; Business coaching; Coaching intervention; SDG-8: Decent work and economic growth